Growth and Structural Properties of ZnO and Zr Doped ZnO Nanostructures by Low Cost Spray Pyrolysis Technique - Gokulakrishnan1, V.; Jeganathan3, K.; Ramamurthi1, K. (Asian Journal of Chemistry, 2013)
Semiconductor nanostructures have attracted increasing interest in the recent past due to their novel device applications. ZnO and Zr doped ZnO nanostructures with different morphologies were prepared by spray pyrolysis method on corning glass substrates and these nanostructures were characterized for their structural, surface morphological and optical properties. The XRD patterns show that Zr doped ZnO nanorods belong to the hexagonal wurtzite structure of ZnO.